Monitoramento de Palpita forficifera (Munroe, 1959) (Lepidoptera: Crambidae) em pomar de oliveira - Silva, Jéssica Maus da (2022)
Palpita forficifera (Munroe, 1959) (olive leaf moth), is a species native to South America and in recent years has been identified as the main pest of the crop. The damage is associated with their eating habits, where the immature ones consume the buds of the plants that will produce the fruits the following year. Olive culture is responsible for the production of olive oil and olives, in Brazil the species was recently introduced, so there are still some issues mentioned by farmers, especially pest management. The work was divided into two studies, the first entitled as “Entomofauna associated with different cultivar of Olea europaea (Linnaeus, 1753)”, aimed to evaluate the composition of the insect fauna present in the crowns of three olive cultivars and to analyze the influence of the nutritional composition of the trees on the attractiveness of the entomofauna. For this, the insects were collected using the canopy net method and later identified and grouped into predators, parasitoids and pest species. The nutritional composition was evaluated through analysis of plant tissue, in which the levels of macro and micronutrients were observed. For the analysis of the insect fauna, the ecological parameters of abundance, richness, diversity and uniformity of the insect fauna were determined. The nutritional composition was related to the presence of insects through Spearmann's correlation analysis. The second work entitled “Population dynamics of Palpita forficifera (Munroe, 1959) and recognition of natural enemies in olive trees”, aimed to verify the population fluctuation of P. forficifera (Munroe, 1959) and to identify the natural enemies present in an olive orchard in the municipality of Formigueiro, Rio Grande do Sul. Monitoring was carried out monthly for a period of one year. Light traps were used to capture the entomofauna. Insects were identified and characterized between natural enemies and pest species. Faunal indices of dominance, abundance, frequency and constancy, diversity and evenness were evaluated. In this context, it is observed that the occurrence of P. forficifera (Munroe, 1959) is predominant in the olive orchard, and the chemical element manganese, available in olive leaves in low concentrations, provides a higher incidence of this insect pest. In the olive grove, several insect species belonging to natural enemies were reported, which in the future may become promising in the development of an integrated pest management (IPM).